Efficacy of Revolution®Plus in cats for the prevention of Dipylidium caninum transmission by infected Ctenocephalides felis - Lindsay Weaver; Alta Viljoen; Riaan Maree; Lina D’Hanis; Shelby Jones; Jane Tonso; Reinier Zweiger; Julian Liebenberg; Vickie L. King; Keith Baker; Jessica Rodriguez; Chris Adolph; et al. (Parasites & Vectors)
Abstract Background Revolution® Plus is a topical combination drug product containing selamectin and sarolaner that has been proven effective against the cat flea Ctenocephalides felis, the intermediate host of the cestode Dipylidium caninum. Here, we report two studies evaluating the efficacy of a single administration of Revolution Plus in preventing D. caninum infection in cats for 1 month through killing of the flea intermediate host. Methods Two studies (study 1 and 2) with the same design were conducted. In both studies, 2 treatment groups of ten cats each were enrolled. On Day 0, the cats in group 1 were treated with a placebo, and the cats in group 2 were treated with Revolution Plus at the minimum recommended dose of 6.0 mg/kg selamectin and 1.0 mg/kg sarolaner. After treatment on Day 0, as well as on Days 7, 14, 21, and 30, the cats in both treatment groups were infested with 100 (± 5) unfed, D. caninum-infected fleas. Live flea counts were conducted on Day 33 (72 ± 2 h after Day 30 infestation). All cats were euthanized on Day 58, and necropsies were performed to enumerate D. caninum scolices in the gastrointestinal tract. Results In both study 1 and 2, all placebo-treated cats were infested with two or more D. caninum scolices at necropsy. Significantly lower mean flea counts were recorded for the Revolution Plus-treated cats compared with placebo-treated cats (P ≤ 0.0001), and efficacy based on least squares mean flea counts on Day 33 was 100% (in study 1) and 94.3% (in study 2). Scolex counts were also significantly decreased in Revolution Plus-treated cats compared with placebo-treated cats, with a 97.1% efficacy in study 1 and a 99.3% efficacy in study 2. Conclusions One topical administration of Revolution Plus at the minimum dosage of 6.0 mg/kg selamectin and 1.0 mg/kg sarolaner provided high efficacy in the prevention of D. caninum infection through the killing of its vector, C. felis, for an entire month. Graphical Abstract